2018
DOI: 10.3171/2016.11.jns162322
|View full text |Cite
|
Sign up to set email alerts
|

Associations between clinical outcome and navigated transcranial magnetic stimulation characteristics in patients with motor-eloquent brain lesions: a combined navigated transcranial magnetic stimulation–diffusion tensor imaging fiber tracking approach

Abstract: OBJECTIVE Navigated transcranial magnetic stimulation (nTMS) and diffusion tensor imaging fiber tracking (DTI FT) based on nTMS data are increasingly used for preoperative planning and resection guidance in patients suffering from motor-eloquent brain tumors. The present study explores whether nTMS-based DTI FT can also be used for individual preoperative risk assessment regarding surgery-related motor impairment. METHODS Data derived from preoperative nTMS motor mapping and subsequent nTMS-based tractography … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
58
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(65 citation statements)
references
References 45 publications
5
58
0
2
Order By: Relevance
“…We concluded that a distance of 10 mm between tumor border and CST was sufficient to preserve motor function. Comparable results were also cited in some prior studies 33,35,37) . The tumor-CST distance may well be regarded as presumptive predictor of outcome, attributable in part to tumor edema.…”
Section: Improvement In Outcomessupporting
confidence: 88%
“…We concluded that a distance of 10 mm between tumor border and CST was sufficient to preserve motor function. Comparable results were also cited in some prior studies 33,35,37) . The tumor-CST distance may well be regarded as presumptive predictor of outcome, attributable in part to tumor edema.…”
Section: Improvement In Outcomessupporting
confidence: 88%
“…The increasing use of non‐invasive mapping techniques for preoperative diagnostics has been accompanied by a change in the tumour resection strategy towards a more quality‐of‐life‐oriented, function‐preserving surgical approach over the last decades. As compared with historical cohorts from the 1980s to early 2000s with rates of surgery‐related deterioration of motor function in the range of 60% (transient; 26–38% permanent) (Magill, Han, Li, & Berger, 2018; Raffa et al, 2018), resection of motor‐eloquent brain tumours has become safer since more effort has been made to assess the functional limits of MC areas for surgery using non‐invasive methods: with 35% transient and 5% permanent surgery‐related motor deficits, the outcome results of the glioma patients in our cohort agree relatively well with the recent literature reporting new postoperative motor deficits in the range of 23–29% (transient) versus 8–22% (permanent) after nTMS‐ and DCS‐guided resection of motor‐eloquent gliomas (Hendrix et al, 2016; Rosenstock et al, 2017; Sollmann et al, 2018). However, the relatively high percentage of transient motor deficits in our cohort might be a consequence of considering (even mild) isolated face muscle impairments as surgery‐related motor deficit ( n = 4, that is, 20% of all patients).…”
Section: Discussionsupporting
confidence: 90%
“…However, a non-invasive method of determining tumor-related neural degradation would be advantageous. In the context of intracranial tumor resection, DTI has mainly been used for preoperative surgical planning [ 18 ], but increasingly is being explored for use as an anatomical/pathophysiological tool for brain tumor prognosis and analysis. However, information derived from fiber tract analysis must be interpreted with caution due to the difficulty in differentiating tumor from edema, particularly with respect to glioma.…”
Section: Discussionmentioning
confidence: 99%